1995
DOI: 10.1104/pp.107.2.593
|View full text |Cite
|
Sign up to set email alerts
|

Light-Regulated and Organ-Specific Expression of Types 1, 2, and 3 Light-Harvesting Complex b mRNAs in Ginkgo biloba

Abstract: In a prior study (E. Chinn and J. Silverthorne [1993] Plant Physiol 103: 727-732) we showed that the gymnosperm Ginkgo biloba was completely dependent on light for chlorophyll synthesis and chloroplast development and that expression of light-harvesting complex b (Lhcb) mRNAs was substantially increased by light. However, dark-grown seedlings that were transferred to constant white light took significantly longer than angiosperm seedlings to initiate a program of photomorphogenesis and the stems failed to gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Similar absolute expression levels have been reported for tomato (Lycopersicon esculentum), in which total steady-state Lhcb mRNA levels in light leaf was approximately 0.75 fmol g Ϫ1 total RNA (Kellmann et al, 1993). These values are in accordance with those determined in a previous study for the absolute value of Lhcb mRNA in light-grown G. biloba leaf (approximately 0.14 fmol g Ϫ1 total RNA; Chinn et al, 1995). However, through analysis of Lhcb expression in this and a parallel study (S. Christensen, E. LaVerne, G. Boyd, and J. Silverthorne, unpublished data), it is apparent that large variations in response timing and magnitude exist (a) between independent light treatments on the same batch of seedlings, and (b) between seedlings from different batches of seed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar absolute expression levels have been reported for tomato (Lycopersicon esculentum), in which total steady-state Lhcb mRNA levels in light leaf was approximately 0.75 fmol g Ϫ1 total RNA (Kellmann et al, 1993). These values are in accordance with those determined in a previous study for the absolute value of Lhcb mRNA in light-grown G. biloba leaf (approximately 0.14 fmol g Ϫ1 total RNA; Chinn et al, 1995). However, through analysis of Lhcb expression in this and a parallel study (S. Christensen, E. LaVerne, G. Boyd, and J. Silverthorne, unpublished data), it is apparent that large variations in response timing and magnitude exist (a) between independent light treatments on the same batch of seedlings, and (b) between seedlings from different batches of seed.…”
Section: Discussionsupporting
confidence: 92%
“…The relative abundance of Lhcb1, Lhcb2, and Lhcb3 mRNAs in light-grown leaf was determined in a previous study (Chinn et al, 1995). Lhcb1 mRNA was found to be the most abundant species, representing approximately 0.14 femto mol g Ϫ1 total mRNA, whereas Lhcb2 and Lhcb3 mRNAs were found to be expressed at 10-to 15-fold lower levels (approximately 10 atto mol g Ϫ1 total mRNA).…”
Section: Lhcb Gene Expression In G Biloba Is Modulated By the Circadmentioning
confidence: 95%
See 1 more Smart Citation
“…When a similar comparison was made using the type 2 pine sequences, Lhcb2*Ppl was 86 to 99% identical with other pine sequences and Lhcb2*Pp2 was 95 to 98% identical. The P. palustris Lhcb sequences were also closely related to G. biloba type 1 and type 2 Lhcb sequences, showing between 85 and 97% identity at the amino acid level (Chinn and Silverthorne, 1993;Chinn et al, 1995). Since a previous study of LHCIIb accumulation in P. palustris indicated that the major polypeptides were expressed in the absence of light (Canovas et al, 1993), sequence-specific probes were constructed to determine whether individual Lhcb mRNAs are also expressed in the absence of light.…”
Section: Resultsmentioning
confidence: 99%
“…Micrograph of a small section of a 22K Arabidopsis DNA microarray hybridized with labeled cRNAs from the control (Cy3) and dark-treated (Cy5) plants. The microarray was scanned using an Agilent scanner to produce the image, which was then analyzed to identify up-regulated (red-spot) or down-regulated (green spots) gene expression in the darktreated Brassica rapa as shown in Table 1. tein complex in Photosystem II (PSII) [9]. The protein is located in the thylakoid membrane and is significant in allowing the thylakoid to collect the light and deliver the derived excitation energy to PSII in a controlled manner.…”
Section: Resultsmentioning
confidence: 99%